2017
DOI: 10.1515/humor-2016-0096
|View full text |Cite
|
Sign up to set email alerts
|

Maladaptive Humor Styles as Mediators of the Relationship Between Attachment Insecurity and Emotion Regulation

Abstract: Although theory and research evidence indicate that less securely attached persons are more likely than their secure peers to experience emotion regulation difficulties, this is not necessarily a pre-ordained outcome. Emotion regulation difficulties may be more proximally predicted by individuals’ maladaptive psychological defenses such as humor styles. This study explored the interrelationships between adult attachment orientations (attachment anxiety and avoidance) and perceived bonds with parents (perceived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…With regard to CR, no significant associations emerged with the two attachment-related dimensions. Yet, prior research reported negative correlations between the anxiety and avoidance subscales of the ECR and CR among adults (i.e., Poncy, 2017). Similarly, Gresham and Gullone (2012) found a bivariate association between perceptions of relationships with parents based on the three dimensions of the Inventory of Parent and Peer Attachment (Armsden & Greenberg, 1987) and the endorsement of CR in children and adolescents.…”
Section: Discussionmentioning
confidence: 89%
“…With regard to CR, no significant associations emerged with the two attachment-related dimensions. Yet, prior research reported negative correlations between the anxiety and avoidance subscales of the ECR and CR among adults (i.e., Poncy, 2017). Similarly, Gresham and Gullone (2012) found a bivariate association between perceptions of relationships with parents based on the three dimensions of the Inventory of Parent and Peer Attachment (Armsden & Greenberg, 1987) and the endorsement of CR in children and adolescents.…”
Section: Discussionmentioning
confidence: 89%
“…Maladaptive humor was found to mediate the relationship between early maladaptive schema domains and depression, proving how humor may interact between internalized schemas and mental health [15]. When the role of parental emotional bonds, adult attachment orientations, and maladaptive humor styles in emotion regulation was explored, findings showed that both adult attachment anxiety and attachment avoidance positively predicted the use of maladaptive humor styles [16].…”
Section: Humor and Attachmentmentioning
confidence: 95%